KEBIJAKAN PENDIDIKAN ISLAM DALAM MENGHADAPI ERA SOCIETY 5.0 - Al Khadziq, Muhammad Fuadzy; Suwadi, Suwadi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
This article explains the progress of the times, especially in the field of technology, the change in the era of society 4.0 to 5.0 also has an impact on the world of Islamic education where all components of Islamic education must prepare themselves to face the era of society 5.0. This article was written using a descriptive qualitative approach. The type of research used is library research. This research was conducted using data collection methods from various literature such as books and journals. The author explores the existing literature and examines it in conducting research. The analytical method used is the descriptive-analytic method, namely explaining and collaborating on the main ideas on the topic of discussion, and presenting them critically through sources related to the theme. The results of the study show that the era of Society 5.0 is a concept of society that places humans and technology as the main focus, this transformation also has a significant positive impact on human life by giving a deeper meaning. Advances in information and communication technology have had a significant influence on the education sector, influencing the development of the creativity of teachers, students and academics. In this Society 5.0 era, teachers as educators need to have digital skills, the ability to think creatively, imaginatively and dynamically in learning in the classroom.